Effects of growth hormone on the ontogenetic allometry of craniofacial bones. Issue 2 (4th March 2013) - Gonzalez, Paula N.; Kristensen, Erika; Morck, Douglas W.; Boyd, Steven; Hallgrímsson, Benedikt
SUMMARY Organism size is controlled by interactions between genetic and environmental factors mediated by hormones with systemic and local effects. As changes in size are usually not isometric, a considerable diversity in shape can be generated through modifications in the patterns of ontogenetic allometry. In this study we evaluated the role of timing and dose of growth hormone (GH) release on growth and correlated shape changes in craniofacial bones. Using a longitudinal study design, we analyzed GH deficient mice treated with GH supplementation commencing pre‐ and post‐puberty. We obtained 3D in vivo micro‐CT images of the skull between 21 and 60 days of age and used geometric morphometrics to analyze size and shape changes among control and GH deficient treated and non‐treated mice. The variable levels of circulating GH altered the size and shape of the adult skull, and influenced the cranial base, vault, and face differently. While cranial base synchondroses and facial sutures were susceptible to either the direct or indirect effect of GH supplementation, its effect was negligible on the vault. Such different responses support the role of intrinsic growth trajectories of skeletal components in controlling the modifications induced by systemic factors. Contrary to the expected, the timing of GH treatment did not have an effect on catch‐up growth. GH levels also altered the ontogenetic trajectories by inducing changes in their location and extension in the shape space, indicating that differences arose before 21 days and were further accentuated by a truncation of the ontogenetic trajectories in GHD groups.